Uporaba debatnih tehnik pri pouku zgodovine v 2. in 3. letniku gimnazije - Gartner, Miha (Šolsko polje, 2007)
Education debate in Slovenia is gaining importance in recent years and its role in achieving higher levels of knowledge with pupils is indisputable. It is a very useful method in history lessons since it stimulates lessons and motivates pupils to achieve higher goals than merely reproducing stated facts.Some of the characteristics of the education debate, ways of preparationfor the debate, debate formats, meaning and form of argumentation, role of the teacher in leading and evaluating debate and the findings of the pupils' success in the time of one year practical use of debate in history lessons will be presented in the paper. The author gained his experience in the time of his mentorship over the debate club and with practising debate in history lessons in 2nd and 3rd year of Gimnazija Celje-Center grammar school.
Keywords: argumentacija; debata; gimnazije; metodika; pouk; retorika; učne metode; zgodovina